Philosophy, Politics, And Economics - PO41 - 202301 - Awapara Franco, Omar (2023)
This course introduces you to basic tools from economics that are used in the analysis of social and political phenomena. We touch upon some issues in the philosophy of economics, but the main focus is on economic methods that can applied to the study of social and political phenomena, including democratic government.